Analytical study on indications of primary cesarean section in tertiary care hospital - Ballu, Arpitha S.; B., Asha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Cesarean delivery is a commonest obstetric surgical procedure performed. WHO stated that regional cesarean section rate should not exceed 10 to 15%. However in many countries cesarean delivery has increased steadily over years. Hence present study is conducted to analyze various indications of primary cesarean section in a tertiary hospital, with an aim to reduce cesarean section rate. Methods: This is a retrospective study conducted in Cheluvamba hospital, Mysore Medical College Research Institute, Mysore, which is a tertiary care centre. For a period of 6months from 1st June 2018 to 31st November 2018 Inclusion criteria: All primary cesarean section done at Cheluvamba hospital during study period were included. Exclusion criteria: Previous cesarean section, patients with previous history of laparotomy done for any obstetric or gynecological cause were excluded. Results: During the study period there was 3799 number of cesarean section. Amongst these 983 cases were primary cesarean section done for varying indications. Hence the rate of cesarean section in our hospital is 25.87%. There were 40.3% cases of fetal distress, failed induction (13.6%), breech (10%), CPD (8%), IUGR with poor BPP (1.8%) Ante partum haemorrhage (3%), DTA (3.5%). Conclusions: From our study, we would conclude that rising trend in cesarean section is an alarming issue. Measures need to be taken to reduce cesarean delivery like Regular use of partograph, Judicious use of amniotomy, oxytocin with inducing agents, Expertization of skills to conduct instrumental vaginal delivery, which is a lost art in modern obstetrics.